Reward and Punishment in Early Childhood Islamic Education: An Integrative Review Towards an Affirmative-Negotiative Model of Islamic Habitus - Nadlifah; Maemonah (Jurnal Pendidikan Agama Islam, 2026)
Purpose  – This integrative review examines how reward and punishment are conceptualized across three distinct scholarly traditions behaviorist psychology, classical Islamic pedagogy, and contemporary Islamic critical pedagogy and synthesizes these perspectives to develop an affirmative-negotiative model for shaping Islamic habitus in early childhood. Design/methods/approach – Whittemore & Knafl's (2005) five-stage integrative review method was employed: (1) problem identification, (2) literature search across multiple databases (Scopus, Google Scholar, Garuda, Al-Maktabah Al-Shamela), (3) data evaluation using CASP and relevance assessment, (4) data analysis through reduction, display, comparison, and conclusion drawing, and (5) presentation of the synthesized model. Findings – The review reveals three key findings. First, current reward and punishment practices tend toward mechanical behavioral control, producing compliance without moral awareness. Second, despite epistemological differences, the two perspectives converge on critical points: punishment must not be repressive, and reward functions as positive reinforcement. Third, Islamic perspectives (classical and contemporary) uniquely contribute spiritual, ethical, and intentional dimensions specifically targhib/tarhib, rahmah, ta'dib, and dialogue-based correction that are absent in behaviorism. Research implications/limitations – The article proposes an affirmative-negotiative model: reward as affirmation of Islamic values cultivating intrinsic motivation, punishment as educative consequence accompanied by child-centered dialogue and reflection. Originality/value – This is the first integrative review to systematically synthesize behaviorist, classical Islamic, and contemporary Islamic perspectives on reward and punishment within Bourdieu's habitus framework, producing a novel model specifically for Islamic early childhood education.